How are we doing? A tool to reflect on the process, progress and priorities of your multi-stakeholder forum - Sarmiento Barletti, Juan Pablo; Larson, Anne M.; Cisneros, Natalia; Heise, Nicole; Liswanti, Nining; Mariño, Harlem; Tamara, Ade (Center for International Forestry Research, 2020)
This handbook explains how to implement How are we doing?, a tool that enables participatory reflective monitoring in multi-stakeholder forums (MSFs). MSFs are spaces that include a wide range of stakeholders in a topic or region, to engage in dialogue, decision making and/or the implementation of activities for common landscape goals. How are we doing? supports enabling conditions to allow the MSF to achieve its goal(s) equitably and effectively. Here we provide a step-by-step process on how to do that. MSFs have gained much attention around the world because of their potential to improve collaboration between different actors, sectors and governance levels to address complex challenges, which cannot be resolved by one actor alone. They can also include actors that, throughout history, have not been able (or allowed) to participate in decision making on land use and land-use issues and/or the design of initiatives that may affect their rights, territories, lives and livelihoods. This handbook is the product of collaboration between members of MSFs and researchers from the Center for International Forestry Research (CIFOR). The collaboration emerged from the identification of the need for a simple tool to allow MSF participants to monitor their forums, and reflect upon and improve their processes and results. In response, CIFOR held a series of participatory workshops in Indonesia and Peru to develop How are we doing?, to reflect on and learn from what the MSF has been doing well (and not so well); examine progress toward the objective(s), including the challenges faced and the ones still ahead; and support the annual planning process. How are we doing? has three main features that set it apart from other tools. First, it was developed together with members of several subnational MSFs. Second, it was designed to be used by MSF participants themselves, not to be applied by external evaluators. And, third, its objective goes beyond a simple assessment of indicators, rather inviting participants to discuss and reflect on their answers. The purpose of this reflection is to learn from the past, consider progress and obstacles to further progress, and collectively plan how to achieve the MSF’s goals in the future